The perspective of rural producers and free market traders in Manaus (AM) on the application of management controls - Corrêa , Gabrielle Cardoso Priess; Ribeiro, Jayandra Karine Corrêa; Carneiro , Leandro Marcondes; Matos, Nyalle Barboza; Oliveira, Elisângela Leitão de; Dias, André Petzhold (Seven Editora, 2023)
The scope of this study aimed to verify the importance of Managerial Accounting as a facilitator tool in rural areas, whether in the production or commercialization of generated products. This management instrument allows for more precise decision-making, cost control, and result analysis through accounting information. For this purpose, a questionnaire was applied to generate a data survey suitable for a descriptive methodology, enabling the identification of the need for mechanisms that assist in the management of rural activities. Throughout this research, it was found that the majority of rural producers and traders in the open-air markets of Manaus (AM) consider its use important, but they rarely appropriate managerial tools into their routines. Even if they are interested, they often lack sufficient knowledge, in addition to dealing with the absence of governmental support or capital, which prevents them from integrating these tools to manage their activities. DOI:https://doi.org/10.56238/alookdevelopv1-180